The Influence of Organizational Culture and Knowledge Sharing on Innovative Work Behavior at RS. Sentra Medika North Minahasa. - Hanna, Febriany Adel; Tamengkel, Lucky F; Rumawas, Wehelmina (Productivity, 2024)
The importance of organizational culture and knowledge sharing in achieving innovation is reinforced by their influence on the innovative work behavior of employees. A culture that supports innovation creates motivation for employees to try new things and overcome the fear of failure. Knowledge sharing facilitates the exchange of valuable information, encourages new ideas, and fosters innovative solutions. In the context of hospitals, organizational culture issues include violations against employees and negligence in medical care for patients. On the other hand, in knowledge-sharing practices, a lack of responsibility in sharing knowledge hampers employee performance. To address these issues, hospitals need to develop a comprehensive strategy that includes changing organizational culture, improving knowledge sharing, providing innovation training, and ensuring strong leadership support. This research is a quantitative study with inner model analysis and outer model analysis assisted by software, namely SmartPLS. The study involved a sample size of 100 respondents, and the results indicated that organizational culture has a positive and significant impact on innovative work behavior in the performance of employees at RS. Sentra Medika North Minahasa. Organizational culture also has a positive and significant impact on knowledge sharing, and knowledge sharing has a positive and significant impact on innovative work behavior at RS. Sentra Medika North Minahasa.